Active Vibration Control of Linear and Nonlinear Quarter Car Suspension System Using PID and Fuzzy Logic Controllers (University of Thi-Qar Journal for Engineering Sciences, 2013)
A quarter car suspension linear and nonlinear models are considered for the investigation of active vibration control using PID (Proportional-Integral-Derivative) and Fuzzy logic controllers. Simulation of the models using matlab-simulink have been built in this work for passive and active vibration control. The Fuzzy rules and memberships were taken from the literature based on practical experience. A comparison between the linear and nonlinear models using different type of control methods have been carried out. Results shows that the Fuzzy-PID control method is the best among other methods, and the nonlinear model gives better results than the linear model for active control.